Prevalence of Complains and Rehabilitation Needs in 150 Patients - Ahmad Ali Akbari-Kamrani (University of Social Welfare and Rehabilitation Sciences, 2001)
Objective: Many studies and researches have been done regarding elderly care health in countries with approved geriatrics as an independent branch. Because geriatrics is a new subject in Iran, this study was done in order to assess about social conditions and prevalence of elderly complaints and their rehabilitation services. Materials & Methods: This is a descriptive study. 150 elderly who were admitted ambulatory in the educational, research and rehabilitation center for older people in 1999, were assessed, and required information were taken. Results: 150 elderly patients assessed, 58% female, 42% male, minimum age: 55 years. Maximum age: 100 years, 17.3% were illiterate, 19.3% had college studies. In female group 13% were widows and in male group 1.2% were widowers. 2 women and 1 man had never married. Cardio pulmonary disorders were the most common complaints (63.3%), then musculoskeletal disorders (55.6%), psychological disturbances (24.6%), neurological disorders (18%), 35% of above cases received physiotherapy, 13% occupational therapy and 2% speech therapy. Conclusion: It seems that in our community, rehabilitation services are given less than the countries with approved geriatrics medicine. Perhaps the role of rehabilitation in the quality of elderly life, for both, patients and their physicians is ignored. It is suggested that, rehabilitation disciplinary must be introduced more than before to physicians, especially who are working in the field of geriatrics.